(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In fine art, it is intended to create and strengthen a unique work on national themes, focusing on creating a finished work based on the laws and regulations, creating a composition in various directions related to the landscape genre, depicting paintings on national themes. Depending on the depicted scenes, it is possible to distinguish the rural, urban (including architecture - veduta - and industrial) landscape. A special field can be an image of a marine element - a seascape or a marina genre. At the same time, landscapes can be both camera and panoramic. In this case, it is important that the creator describes what situation he wants to reflect and how skillfully he describes it.